Nucleoside and Oligonucleotide Modification for Targeting the DNA Damage Repair Enzyme SNM1A - Fay, Ellen (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2024)
The exonuclease SNM1A is a key enzyme involved in the repair of interstrand crosslinks, a highly cytotoxic form of DNA damage. As cells depleted in this enzyme display increased sensitivity to chemotherapeutic agents such as cisplatin, SNM1A is a potential target for the treatment of cancers that have developed resistance to traditional chemotherapeutics. The study of SNM1A presents formidable challenges, primarily attributed to its markedly low expression levels and the inherent difficulties associated with achieving stable overproduction from mammalian cells. There remains a need for improved chemical and biochemical tools to facilitate the study of SNM1A. The work described within elaborates on previous results from the McGouran Group which identified that nucleosides and oligonucleotides, incorporating metal-binding groups, can successfully target the metal ions in the SNM1A active site. Initially, the expansion of established inhibitor scaffolds was investigated for generating tools to study SNM1A. This involved probing the utility of a malonate group as both a metal-binding group and a functionalisation handle. Subsequently, nucleobase modification was examined as a strategy to incorporate a functionalisation handle into established inhibitor frameworks. A thymidine derivative, based on a reported inhibitor, was designed to include a 5?-hydroxamic acid metal-binding group and a propargyl handle on the N3?position. Surprisingly, this compound showed limited inhibitory activity compared to its parent compound. The results indicated the importance of the N3-position for recognition of thymidine derivatives by SNM1A. Novel carboxylate-rich nucleoside analogues, featuring succinic, aspartic, glutamic and citric acid-derived 5?-modifications were also evaluated for their ability to target SNM1A. The succinic acid series demonstrated particular activity. The most effective inhibitor was a 5-methyluridine derivative with a 5?-succinic acid modification. A real?time fluorescence assay was employed to determine an IC50 for inhibition of SNM1A by this 5-methyluridine derivative. To further validate its mechanism of action as binding to the SNM1A active site, the ability of this inhibitor to bind to DNA was examined using a circular dichroism-based assay. The 5-methyluridine-derived inhibitor is the most potent nucleoside-based inhibitor of SNM1A reported to date. A two-step validation method was devised to assess the suitability of metal-binding groups for targeting SNM1A. A fragment-based screening approach was first employed to identify metal-binding fragments with the ability to target the enzyme. Effective fragments were then incorporated into oligonucleotide strands via the copper-catalysed azide-alkyne cycloaddition reaction. These tailored oligonucleotides hindered SNM1A activity at concentrations >1000-fold lower than their fragment counterparts. This innovative strategy of integrating functional fragments into oligonucleotides holds broad applicability for crafting modified oligonucleotides with affinity for DNA damage repair enzymes. Oligonucleotides featuring artificial backbones were explored for targeting SNM1A. A series of dinucleoside phosphoramidites, containing unnatural internucleoside linkages, were generated and incorporated into oligonucleotides via solid-phase oligonucleotide synthesis. Oligonucleotides containing urea, squaramide, thioacetamide and sulfinyl acetamide linkages were examined for targeting SNM1A using a gel electrophoresis?based assay. The binding ability of the oligonucleotides was further evaluated using a real-time fluorescence assay to determine IC50 values. This approach proved successful in generating oligonucleotides with notable affinity for SNM1A, as all of the modified oligonucleotides demonstrated increased inhibition levels compared to an unmodified oligonucleotide. Overall, the findings presented in this work mark substantial advancements in the tailored modification of nucleosides and oligonucleotides for targeting SNM1A. The discerned insights will not only guide the design of next-generation inhibitors but also pave the way for the construction of chemical probes, facilitating in vivo studies of SNM1A and, by extension, contributing significantly to the broader landscape of DNA damage repair mechanisms.
APPROVED
Keywords: DNA repair; oligonucleotide modification; nucleoside modification; metal-binding group